cosa-sina 1

Prove that (cosA-sinA+1)/(cosA+sinA-1)=cosecA+cotA TRIGONOMETRY

Prove that (CosA - SinA + 1)/(CosA + SinA -1) = CosecA + CotA. | Class 10 | Tarun sir |

cos a-sina+1/cosa+sina-1=coseca+cota

Prove that 1+cosA/sinA = sinA/1 - cosA, trigonometry, class 10

cosA-sinA+1/cosA+sinA-1 = cosecA + cotA Explain in Just 2 Min | cbse class 10 | #trigonometry

Prove that (CosA - SinA + 1)/(CosA + SinA -1) = CosecA + CotA. | Class 10th | Tarun sir |

(cosA-sinA+1)/(cosA+sinA-1) = cosecA + cotA

Prove That cosA- sinA+1/cosA+sinA-1 = cosecA+ cotA |class 9| class 10

(cosecA – sinA)(secA – cosA) = 1/tanA+cotA Class 10th maths trigonometry PYQ (2022A II)

Prove that:cosA-sinA+1/cosA+sinA-1=cosecA+cotA|Trigonometric|Aimers|prove that question|opt maths|

Prove that 1+cosA+sinA/1+cosA-sinA =1+sinA/cosA

cosa-sina+1/cosa+sina-1 Trigonometric Identities Class 10 Maths

cosA- sinA+1/cosA+sinA-1=C𝑜secA+CotA | Prove the Identity Cos⁡𝐴−S𝑖𝑛𝐴+1/C𝑜𝑠𝐴+Sin𝐴−1=C𝑜secA+CotA

If cosA - sinA=1,prove that cosA + sinA=+-1

Prove that (CosA-SinA+1)/(CosA+SinA-1)=CosecA+CotA || Exercise 8.4 Q5 (v) class 10 NCERT

Prove that `(cosA-sinA+1)/(cosA+sinA-1) =cosec A+ cot A` using the identity `cosec^(2)A=1+cot^(2)A`.

if `(2 sina)/{1+cosa+sina}=y`, then `{1-cosa+sina}/(1+sina)=`

prove that cosA-sinA+1/cosA+sinA-1=cosecA+cotA by using the identity cosec^A=1+cot^A#maths #viral

cosA-sinA+1/cosA+sinA-1 = cosecA+cotA

sinA/1+cosA+1+cosa/sinA=2cosecA by SH MATH

(cosA-sinA+1)/(cosA+sinA-1)=cosecA+cotA

Prove that cosA/(1+sinA) + (1+sinA)/cosA = 2secA

CosA/1+SinA+1+SinA/CosA=2 SecA